Scavenger Receptor Class B Type I is Required for 25‐Hydroxycholecalciferol Cellular Uptake and Signaling in Myeloid Cells. Issue 15 (8th July 2020) - Tenesaca, Shirley; Vasquez, Marcos; Fernandez‐Sendin, Myriam; Di Trani, Claudia Augusta; Ardaiz, Nuria; Gomar, Celia; Cuculescu, Doina; Alvarez, Maite; Otano, Itziar; Melero, Ignacio; Berraondo, Pedro
Abstract : Scope: Vitamin D3 is a critical molecule for the properly controlled activity of the immune system. In myeloid‐derived cells, vitamin D3 induces the production of the antimicrobial and antitumor peptide cathelicidin. In this study, the mechanism of the entry of 25‐hydroxycholecalciferol (25(OH)D) in myeloid‐derived cells is explored. Methods and results: Here, a novel regulatory pathway of vitamin D3 biology is described. Using a polyclonal antibody, two different chemical inhibitors, and a high‐density lipoprotein as a competing ligand, it is demonstrated here that the 25(OH)D signaling pathway in myeloid cells depends on scavenger receptor class B type I (SR‐B1). This effect is observed in the THP‐1 monocytic cell line and in human primary monocytes. SR‐B1 blockade abrogates the cellular uptake of 25(OH)D leading to a general shut down of the gene transcription program modulated by 25(OH)D. The results obtained at the transcriptional level are confirmed at the protein and functional level for CD14 in the THP‐1 cell line. Conclusion: In conclusion, SR‐B1 plays a critical role in vitamin D3 biology, paving the way for novel therapeutic interventions. Abstract : Vitamin D3 plays an important role in the immune system, but the circulating form of it must be converted in monocytic‐derived cells. The present study reveals that the Calcidiol is internalized in monocytic cells by the scavenger receptor class B type I and therefore, this receptor is a novel regulatory protein of Vitamin D3 bioactivity.